Junk food consumption among school-age adolescents in Kanakasundari rural municipality, Jumla - Karki, Upendra; Thapa, Janak K.; Sangroula, Raj K.; Chaudhary, Pramodh; Thapa, Salina; Shrestha, Arati D.; Balampaki, Pabitra; Thapa, Alina; Karki, Dipak; Thapa, Deependra K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Junk foods typically contain high calories from sugar or fat with little protein, vitamins, or minerals. This study was conducted to determine the consumption and prevalence of junk food consumed among school-age adolescents. The main aims of this study were to find out the junk food consumption among school-age adolescents (5-18) in Kanakasundari rural municipality. Methods: This was analytical cross-sectional research. The total sample size for the study was 280. Purposive sampling was used to select the schools and census was used to select the students from the schools. A self-administered semi-structured questionnaire in Nepali version was used to collect the data and the collected data were entered and analysed in SPSS using simple statistical methods. Results: Among the 280 respondents, the mean age was 15.17 years. The consumption of junk food among adolescents was 45 percent among males and 55 percent among females. Religion (p=0.011) and type of family (p=0.034) were significantly associated with junk food consumption. The participants following Hindu religion were 3.43 times more likely to be consume junk food (COR=3.430, 95% CI=1.256-9.366) as compared to non-Hindu. Participants residing in joint family were less likely to consume junk food (COR=0.490, 95% CI=0.252-0.954) as compared to nuclear family. Conclusions: Majority of children consumed junk food regularly; the majority preferred it for taste and some were influenced by advertisements. There is a great need to maintain healthy eating habits among adolescents to decrease the health risk associated with frequent junk food.